A Study on the Quality of Modern Kutu Baru Kebaya with Mawar Putri Design Element - Restu Diva Aulia; Sita Nurmasitah (International Journal of Multidisciplinary Sciences and Arts, 2025)
The kutu baru kebaya is a cultural heritage of Indonesia that requires innovation to remain relevant in modern times without diminishing its traditional values. This study aims to analyze the quality of modern kutu baru kebaya products inspired by the Mawar Putri, focusing on aesthetics, ornamentation, design, materials, and finishing aspects. A quantitative descriptive approach was employed, involving four fashion experts as validators to assess the quality of two kebaya prototypes. Data were collected through structured observation using a Likert scale (1–4) assessment sheet. The data were analyzed using descriptive statistics and percentage calculations to determine product feasibility categories. The findings reveal that Kebaya A achieved an average score of 82.71%, classified as “highly feasible,” while Kebaya B attained 86.67%, also categorized as “highly feasible.” Kebaya B outperformed in aesthetic (87.5%), ornamentation (87.5%), and design (81.25%) criteria, whereas both products demonstrated equivalent performance in material (91.67%) and finishing (85.42%) aspects. It can be concluded that both modern kutu baru kebaya designs inspired by the Bunga Mawar Putri rose meet high-quality standards, with Kebaya B exhibiting superior overall performance. Nevertheless, further refinement is recommended, particularly in the application of sequins and embroidery to enhance visual and structural detailing. These findings contribute to preserving cultural identity through contemporary fashion design while highlighting the importance of quality evaluation in traditional clothing innovation.